Influence of BMI on Elastographic Strain Ratios of Achilles Tendon - Mirza, Eraj Humayun; Al-Qahtani, Mahdi; Al-Zahrani, Abdullah; Al-Mujalli, AbdulAziz (British Journal of Healthcare and Medical Research, 2016)
The Achilles tendon have two major problems due to injury; one being a chronic injury called Achilles tendinopathy and the second being acute injury which are more commonly known as Achilles tendon rupture. Changes in stiffness of Achilles tendon is alarming and can cause deleterious effects on quality of life in an individual. Achilles tendon is reported to be affected significantly due to the weight of an individual. The effect of Body Mass Index (BMI) on stiffness of Achilles tendon was evaluated in the current study. Elastography was performed on individuals ranging from 19 to 23 years for detecting the stiffness of the Achilles tendon. Individuals were grouped according to their BMI in 3 categories (underweight, normal and overweight) and their strain ratios were measured. The strain ratio results for all volunteers were ranging from 1.03 to 6 (1.03 for underweight and 6 for overweight). Difference in weight of individuals effect the Achilles tendon stiffness. The overweight individuals had the highest stiffness while the underweight individuals had the lowest. It is concluded that higher stiffness may likely lead to Achilles tendon injury.